2010
DOI: 10.3945/ajcn.2010.29819
|View full text |Cite
|
Sign up to set email alerts
|

Muscle full effect after oral protein: time-dependent concordance and discordance between human muscle protein synthesis and mTORC1 signaling

Abstract: We confirm our previous findings that MPS responses to AAs are transient, even with oral protein bolus. However, changes in MPS only reflect elevated mTORC1 signaling during the upswing in MPS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
329
4
9

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 338 publications
(379 citation statements)
references
References 38 publications
(44 reference statements)
21
329
4
9
Order By: Relevance
“…Although MPS increases after oral consumption (Atherton et al 2010) or I.V infusions of essential AA are well accepted (Anthony et al 2000;Bennet et al 1990;Millward 2012) previous work by our group ) and others (Volpi et al 2000) has demonstrated 'anabolic resistance', whereby older men demonstrate blunted (compared to those in younger men) fed-state increases in MPS. Such anabolic resistance has not only been conjectured by us and others to contribute to the sarcopenia of ageing but it also appears to be a common feature of many kinds of muscle atrophy (e.g.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Although MPS increases after oral consumption (Atherton et al 2010) or I.V infusions of essential AA are well accepted (Anthony et al 2000;Bennet et al 1990;Millward 2012) previous work by our group ) and others (Volpi et al 2000) has demonstrated 'anabolic resistance', whereby older men demonstrate blunted (compared to those in younger men) fed-state increases in MPS. Such anabolic resistance has not only been conjectured by us and others to contribute to the sarcopenia of ageing but it also appears to be a common feature of many kinds of muscle atrophy (e.g.…”
Section: Discussionmentioning
confidence: 98%
“…This finding was based on a 2-hour window of fed-state MPS investigation, the postprandial period that has been well defined by our group (Atherton et al 2010;Mitchell et al 2015a;Mitchell et al 2015b). …”
Section: Discussionmentioning
confidence: 99%
“…The anabolic effect of essential amino acids seems to level off at a total dose of 20-25 g protein day −1 (Tipton and Phillips, 2013). An oral bolus of whey protein has been shown to increase muscle protein synthesis by 300% while muscle protein breakdown is repressed by 50% in young men (Atherton et al, 2010). The increase in muscle proteins synthesis rate is mirrored by mTORC1 activation at least during the first 90 min of the response.…”
Section: Essential Amino Acidsmentioning
confidence: 95%
“…mTORC1 signaling has consistently shown to be activated in response to both muscle loading (e.g., resistance exercise), and amino acid consumption/treatment (Marcotte, West, & Baar, 2015), and as such these stimuli represent excellent candidates as therapies for attenuating the muscle wasting associated with a number of disease states and ageing. Indeed, acute human studies have observed activation of mTORC1 and its downstream targets (e.g., p70S6K, rpS6, and 4EBP‐1) following ingestion of mixed amino acids, and this is coupled with an increase in muscle protein synthesis (MPS) in the ensuing 60–120 min (Atherton, Etheridge et al, 2010; Koopman et al, 2006; Paddon‐Jones et al, 2004; Volpi, Kobayashi, Sheffield‐Moore, Mittendorfer, & Wolfe, 2003). Furthermore, when human skeletal muscle undergoes loading prior to amino acid ingestion this effect on mTORC1 signaling and MPS is potentiated (Moore, Atherton, Rennie, Tarnopolsky, & Phillips, 2011; Witard et al, 2014).…”
Section: Introductionmentioning
confidence: 99%